2020
DOI: 10.3390/ani10091633
|View full text |Cite
|
Sign up to set email alerts
|

Using High-Density SNP Array to Reveal Selection Signatures Related to Prolificacy in Chinese and Kazakhstan Sheep Breeds

Abstract: Selection signature provides an efficient tool to explore genes related to traits of interest. In this study, 176 ewes from one Chinese uniparous breed and three Kazakhstan multiparous breeds are genotyped using Affymetrix 600K HD single nucleotide polymorphism (SNP) arrays, F-statistics (Fst), and a Cross Population Extend Haplotype Homozygosity Test (XPEHH). These are conducted to identify genomic regions that might be under selection in three population pairs comprised the one multiparous breed and the unip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…The gene CDH10 was associated with several reproduction traits in buffaloes [64]. Furthermore, PDIA4 was found to be involved in the litter size in sheep and pigs [65,66]. In our work, LEPR was identified as a candidate gene for the pregnancy rate.…”
Section: Discussionmentioning
confidence: 55%
“…The gene CDH10 was associated with several reproduction traits in buffaloes [64]. Furthermore, PDIA4 was found to be involved in the litter size in sheep and pigs [65,66]. In our work, LEPR was identified as a candidate gene for the pregnancy rate.…”
Section: Discussionmentioning
confidence: 55%
“…In a previous study, population high-density SNP array analysis of multiparous and uniparous sheep revealed that MAPK1 is a selected gene among Kazakhstan sheep (Wang et al, 2020), highlighting its role in reproduction. One synonymous SNV was also identified in MAPK1 (Supplementary Table S15; exon1:c.C144T: p.L48L).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, a signal adequate for promoting trophoblast proliferation and invasion can decrease below thresholds if MAPK1 protein expression is insufficient ( Saba et al, 2003 ; Jeong et al, 2013 ). In a previous study, population high-density SNP array analysis of multiparous and uniparous sheep revealed that MAPK1 is a selected gene among Kazakhstan sheep ( Wang et al, 2020 ), highlighting its role in reproduction. One synonymous SNV was also identified in MAPK1 ( Supplementary Table S15 ; exon1:c.C144T: p.L48L).…”
Section: Discussionmentioning
confidence: 96%
“…Wei et al [ 13 ] used Fst and XP-EHH methods on 122 Chinese native sheep and found that EPASI genes play an important role in hypoxia adaptation. By selective signature analysis between polytocous and monotocous sheep populations, Wang et al identified six genes (ESR1, OXTR, MAPK1, RYR1, PDIA4, and CYP19A1) associated with polytocous traits in sheep [ 14 ]. Yao et al used selective signature analysis between high and low fertility populations in Bamei mutton sheep and found that JUN, ITPR3, PLCB2, HERC5 and KDM4B genes might be associated with polytocous traits [ 15 ].…”
Section: Introductionmentioning
confidence: 99%